• 2022-05-28
    设随机事件A与B互不相容,且P(A)>0,P(B)>0,则( )。
    A: P(A)=1-P(B)
    B: P(AB)=P(A)P(B)
    C: P(A[img=12x16]1803320bcef6cfa.png[/img]B)=1
    D: [img=86x27]1803320bd7a92ff.png[/img]
  • D

    内容

    • 0

      设随机事件A与B互不相容,且P(A)>;0,P(B)>;0,则( )。 未知类型:{'options': ['P(A)=1-P(B)', 'P(AB)=P(A)P(B)', 'P(A[img=12x16]17de759c42d12cc.png[/img]B)=1', ''], 'type': 102}

    • 1

      设随机事件A与B互不相容,且P(A)>0,P(B)>0,则( ). A: P(A)=1-P(B) B: P(AB)=P(A)P(B) C: P(A+B)=1 D: [img=73x29]18030f5124977f6.png[/img]

    • 2

      设随机事件A与B互不相容,且P(A)>P(B)>0,则 A: P(A)=1-P(B) B: P(AB)=P(A)P(B) C: P(A∪B)=1 D: [img=86x30]1803dd36bcbdcb7.png[/img]

    • 3

      设随机事件A与B互不相容,且P(A)>P(B)>0,则 A: P(A)=1-P(B) B: P(AB)=P(A)P(B) C: P(A∪B)=1 D: [img=86x30]1803bf64108f71e.png[/img]

    • 4

      设随机事件A与B互不相容,且P(A)>P(B)>0,则 A: P(A)=1-P(B) B: P(AB)=P(A)P(B) C: P(A∪B)=1 D: [img=86x30]18032f5ec573920.png[/img]